2019
DOI: 10.1002/slct.201900860
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation to Methanol via In‐situ Reduced Cu/ZnO Catalyst Prepared by Formic acid Assisted Grinding

Abstract: Methanol is an essential chemical raw material and potential alternative energy source. In this paper, Cu based catalyst was prepared by the noble solid phase grinding method for CO2 hydrogenation to methanol. The influence of chelating agent, heating rate, calcination temperature and calcination period of the precursor on catalyst performance were studied in depth. The catalyst precursor with formic acid as a chelating agent was reduced in‐situ when calcined in nitrogen (N2) at 573 K. The formic acid was deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…As can be visibly noticed, the pattern of CZZA catalyst exhibited characteristic peaks of both CuO mainly as tenorite (JCPDS 48‐1548) and ZnO as zincite (JCPDS 36‐1451) . It was reported that an intrinsic association between CuO and ZnO species enhances particle dispersion, where ZnO species functions as spacers between metallic Cu particles inhibiting them from aggregation and sintering …”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…As can be visibly noticed, the pattern of CZZA catalyst exhibited characteristic peaks of both CuO mainly as tenorite (JCPDS 48‐1548) and ZnO as zincite (JCPDS 36‐1451) . It was reported that an intrinsic association between CuO and ZnO species enhances particle dispersion, where ZnO species functions as spacers between metallic Cu particles inhibiting them from aggregation and sintering …”
Section: Resultssupporting
confidence: 63%
“…The core CZZA metal catalyst somewhat possess a unique fabrication hinged on its excellent hydrogenation ability associated to Cu−Zn . This is further coupled to an escalated catalytic activity and a remarkable thermal stability, credited to the incorporated Al and Zr for an effective high magnitude intermediate product (methanol) formation .…”
Section: Resultsmentioning
confidence: 99%
“…In Cu-based catalysts, the support with high specific surface area can disperse the active components well and prevent the catalyst from deactivation due to sintering [35]. The traditional supports primarily include Al 2 O 3 [56][57][58], ZnO [59,60], and ZrO 2 [61][62][63]. However, the water generated by the side reaction can accelerate the sintering of the active sites, which leads to the catalyst being relatively easy to deactivate, and Al 2 O 3 has hydrophilic properties, so the development of other carriers to make up for this is necessary.…”
Section: Supportsmentioning
confidence: 99%